Večjezičnost v institucijah Evropske unije - Stritar, Mojca (Jezik in slovstvo, 2009)
With the aid of a written questionnaire, an analysis of the language position of Slovene representatives in working groups and committees of the European Council was undertaken. On the whole, these representatives are satisfied with the interpreting and translation services available, in spite of difficulties such as specialist terminology, technical problems and delays with translations into Slovene. Although interpreting is provided relatively frequently, Slovene representatives use the Slovene language rather rarely, especially in informal situations. The English language prevails, which is also the language of which the Slovene representatives have the best knowledge, while the language that presents them with the most difficulties in communication is French. The use of Slovene language seems most important to the representatives primarily from the symbolic point of view, while in practice they use just one working language. Nonetheless, half of the representatives questioned are in favour of the existing multi-linguistic system within the institutions of the EU, while some of them believe that having English as the only working language would be a functional and financially efficient system.
Keywords: Slovene; slovenščina; večjezičnost; prevajanje; translation; tolmačenje; interpretation; pragmatika